Research on the modernization of the data transmission standard ARINC629 - Kholyavkina, T.V.; Kravchenko M.О. (Problems of Informatization and Management, 2025)
As of 2024, due to its high reliability and efficient data transmission between various aircraft systems, enhancing flight safety and efficiency, the ARINC 629 digital data bus exchange standard is still used in various aircraft models: Boeing 777-200/300/ER/F, Boeing 787-8/9, Boeing 747-8, Airbus A350-900/1000, Airbus A380-800, Embraer E-190/E-195, Bombardier CRJ900/1000, and Sukhoi Superjet 100. The aircraft listed above utilize ARINC 629 for data transmission among different systems: Flight Management System (FMS), Engine Control System (ECS), Air Conditioning (AC), Lighting (L), and Communication (C). The article suggests replacing the signal transmission material with fiber optic technology. Indeed, there are upgrades to this standard in the form of ARINC 818 [11, 12]. However, the implementation of these standards tends to be more specialized and less flexible.